The Relationship Between Hemoglobin Concentration With Maximum Oxygen Volume Levels In Obese Female - Aryaputra, Aryaputra; Purwanto, Bambang; Widodo, Achmad (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to analyze the relationship between hemoglobin concentration and maximal oxygen volume in obese women. This study used a cross sectional study method using 40 obese women aged 18-22 years, body mass index 25-35 kg/m2 and percentage body fat above 30%, normal blood pressure, resting heart normal rate and fasting blood glucose below 100 mg / dL. Measurement of Hb concentration using Easy Touch with a unit concentration of g/dL, while VO2max measurement using the Astrand 6-minute cycle test method. Data analysis techniques used the Pearson Correlation test. The results obtained mean Hb (15,365±1,467) g/dL and VO2max (28,635 ± 4,256) ml/kg /min. Based on the results of the study concluded that there is a positive correlation between Hb levels with maximum oxygen capacity in obese women. Further research is needed to explain the physiological mechanism of the relationship between hemoglobin concentration and maximal oxygen volume in more detail